QUANTIFIERS IN UZBEK: ANALYTICAL STUDY - Sayidmurod S. Abdurahmonov,; Gwangrak Son, (Research Focus International Scientific Journal, 2026)
This paper investigated quantifiers in the Uzbek language, focusing on floating quantifiers, numerals, and the differences between floating quantifiers and determiner quantifiers. It raises the question of whether floating quantifiers in Uzbek appear in the position of adverbs by default or whether they are stranded when their complement moves to Spec-IP. Furthermore, this study examines the structure, classification, and distribution of quantifiers in Uzbek. It also discusses the derivation of genitive and double-case quantifiers. A key question addressed is whether Uzbek quantifiers are derived through A-movement or A'-movement. As a result, it can be observed that quantifier floating appears as a combination of DP within GEN and DCQ structures, whereas AQ does not exhibit floating properties. Ordinary quantifiers are always adjuncts within DP. Based on the discussion above and derivations from partial and double DPs, the structure of floating quantifiers in Uzbek is internal and involves A'-movement. Further research is needed to determine whether Uzbek floating quantifiers are stranded or function adverbially.